ANALISIS PENGENDALIAN MUTU DALAM MENINGKATKAN PROSES PRODUKSI - Elin Herlina; Faizal Haris Eko Prabowo; Dea Nuraida (Jurnal Fokus Manajemen Bisnis, 2021)
This research is motivated by the still not optimal quality control in the production of Nata De Coco which can be seen from the decrease in customer satisfaction, namely the reduced demand for products from consumers, this is thought to be caused by the not optimal implementation of quality control carried out by the company. The research method used in this study is a qualitative descriptive research method. Based on the results of the study that: 1) The implementation of quality control at the Nata De Coco Factory Bojongmengger Ciamis has been carried out quite well in accordance with the indicators that have been set in this study, namely performance, features, reliability, conformance, durability, service ability, aesthetics and quality which shows that it is quite good; 2) The production process at the Nata De Coco Factory Bojongmengger Ciamis is generally good because it is in accordance with the indicators that have been set in this study, which include the production schedule, production sequence and production time which show that it is good; 3) The implementation of quality control plays a role in improving the production process at the Nata De Coco Factory Bojongmengger Ciamis. It can be seen that with the implementation of quality control which is already quite good, it has an impact on increasing the production process at the Nata De Coco Factory in Bojongmengger Ciamis. Thus, if the implementation of quality control is good, the company's production process will increase.